How compensation policy based on EVA performance reduces the conflict between managers and shareholders - Ribeiro, Humberto (2013)
There is a well-known conflict between managers and shareholders, superbly illustrated by the agency theory. A way for shareholders to ensure that managers will perform optimally, by taking the best actions and decisions, is to tie managers’ compensation to the performance of the firms. However, how can we fairly measure their performance? The Economic Value Added (EVA) methodology seems to be a good solution; recent events reinforced the idea that accounting indicators analysis may not be a suitable approach. The EVA is not a widespread concept in Portugal and its inception is relatively recent. To have an idea about how Portuguese managers perceive EVA and to understand which strategies (e.g. wages policy, bonuses, stocks and/or stocks options) firms utilize to make everybody happy, particularly managers, we developed a study with Portuguese public entities, using the questionnaire methodology.